Peak to post-peak thermal history of the Saglek Block of Labrador: A multiphase and multi-instrumental approach to geochronology - Kusiak, M.; Dunkley, Daniel; Whitehouse, M.; Wilde, Simon; Salacinska, A.; Konecný, P.; Szopa, K.; Gaweda, A.; Chew, D. (Elsevier Science BV, 2017)
The Saglek Block of coastal Labrador forms the western margin of the North Atlantic Craton, where Archean gneisses and granulites have been reworked during the Paleoproterozoic. Previous work has established that the block is a composite of Eoarchean to Mesoarchean protoliths metamorphosed to upper amphibolite and granulite facies at around 2.8-2.7. Ga. New in-situ microbeam dating of accessory minerals in granoblastic gneisses reveals a complex peak to post-peak thermal history. Zircon growth at ca. 3.7-3.6. Ga provides the age of formation of the tonalitic protoliths to the gneisses. Further zircon growth in syn-tectonic granitic gneiss and monazite growth in a variety of orthogneisses confirm peak metamorphic conditions at ca. 2.7. Ga, but also reveal high-temperature conditions at ca. 2.6. Ga and 2.5. Ga. The former is interpreted as the waning stages of the 2.7. Ga granulite event, whereas the latter is associated with a younger phase of granitic magmatism. In addition, apatite ages of ca. 2.2. Ga may represent either cooling associated with the 2.5. Ga event or a previously unrecognized greenschist-facies metamorphism event that predates the Torngat Orogeny.